Persepsi Mahasiswa Tentang Penyelenggaraan Program Intensif Bahasa pada Pusat Pengembangan Bahasa - Yeti Nurizzati (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2017)
Abstract: Language Development Center (PPB) IAIN Syekh Nurjati Cirebon is one of the Technical Implementation Unit of higher education related to intensive English and Arabic development program. All students from semester one to four must follow and graduate on this program. Assessment of the implementation of this program based on student perceptions of 100 samples is an evaluative study conducted by researchers. Using a questionnaire as a research instrument, it contains input, process, output, lecturers and staff indicators in the learning process. From the research results obtained conclusion that the assessment of the implementation of language intensive program on PPB IAIN Syekh Nurjati Cirebon based on students' perceptions goes pretty well. Most of the students considered that the lecturers of PPB had prepared the teaching well, mastered the taught material, and the exam questions were in accordance with the taught material. Some things that need to be improved are intensive course lectures held on Saturday Sunday, late module distribution, team teaching implementation that has not been optimal, and poor lecturer behavior.Â Keywords: Language intensive program, Perception